Strategi Konten Budaya Pantun Khas Kalimantan Pada Media Sosial Instagram Diskominfo Kota Pontianak - Suryamaulana, Muhammad Kevin; Setiawati, Sri Dewi (PT ARRUS Intelektual Indonesia, 2024)
This research discusses Thursday's Content Strategy on Social Media on Instagram Diskominfo Pontianak City. This Thursday Berpantun content itself is a regular content owned by the Pontianak City Diskominfo, Kamis Berpantun also includes elements of Malay culture by berpantun to convey information and appeals to the public so that it is easy to understand. The goal is to analyze the Strategy of Thursday Content on Social Media on Instagram Diskominfo Pontianak City, this study uses a qualitative method with data collection through interviews and observations. The results show that overall Thursday content is designed to be a medium that combines entertainment, education, and the delivery of important information through a strong local cultural approach. The process of preparing this Thursday content is by determining the theme to be discussed, writing a rhyme script, filming preparation, editing, publication, and feedback.